2014
DOI: 10.3892/mco.2014.420
|View full text |Cite
|
Sign up to set email alerts
|

Vascular invasion affects survival in early hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) is an aggressive malignant tumor with a high mortality rate. The optimal therapeutic choice for early HCC is surgical resection. However, the rate of intrahepatic recurrence is high. The objective of this study was to evaluate the effect of various factors on the survival of patients with early HCC. Between January 1st, 2006 and December 31st, 2013, a total of 89 patients who underwent surgery for HCC were retrospectively enrolled. The analysis was conducted using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…Vascular invasion has been considered an important prognostic indicator in HCC . However, based on this study, no prognostic ability for vascular invasion was found in the whole population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular invasion has been considered an important prognostic indicator in HCC . However, based on this study, no prognostic ability for vascular invasion was found in the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been identified as prognostic indicators and are incorporated into various staging systems. These factors include lesion numbers, vascular invasion, portal hypertension, regional lymph node metastases, distant metastases, laboratory examination indicators such as serum albumin and bilirubin, and so on. Tumor size has been included in several staging systems, such as the Liver Cancer Study Group of Japan TNM staging system and the Hong Kong staging system .…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al investigated that the 5-year overall survival and recurrence-free survival rates were 77.7% and 59.9% in small HCC patients (maximum tumor size ≤ 3 cm) after resection [ 3 ]. Tumor size, vascular invasion, histological grade and treatment strategy have been considered to be independent risk factors influencing the prognosis of early-stage HCC [ 12 14 ]. In the present research, we identified a total of 233 early-stage HCC patients (solitary tumor, tumor size ≤ 5 cm and no macrovascular invasion).…”
Section: Disscusionmentioning
confidence: 99%
“…PVTT can cause intrahepatic or distant metastasis through the portal system and lead to liver dysfunction and portal hypertension, leading to ascites formation, variceal rupture, hepatic encephalopathy, and/or death [6]. PVTT is an independent predictor of tumor recurrence and is widely accepted as a sign of advanced stage, which frequently leads to a poor prognosis [7,8]. PVTT has categorized into five grades: Vp0, no PVTT; Vp1, distal to the second-order branches; Vp2, in the second-order branches; Vp3, in the right first-order branches; and Vp4, in the main trunk or left first-order branches (or both) ( e Liver Cancer Study Group of Japan) [9].…”
Section: Introductionmentioning
confidence: 99%